Cognitive Competencies of Secondary School Teachers in Jordan from Their Point of View - AL-Momani, Mohammad Omar (International Journal Pedagogy of Social Studies, 2022)
The difficulties facing those in charge of the learning process, especially in the subject of vocational education in the schools of the Jordanian Ministry of Education, are a major obstacle to the failure to achieve the goal of educational trends to raise the generation. Therefore, those in charge of the teaching process must be familiar with general educational trends and professional competence; The purpose of evaluating educational trends in vocational education is to find out their reality and find solutions to them. The current study aims to assess the reality of educational trends and methods of teaching in Jordan by those in charge of them with the aim of advancing them in accordance with the professional competencies they studied and what the reality produces from modern theories and sciences. Consisting of(200)A teacher and a female teacher of vocational education in Jordan. The study concluded that the teachers’ performance is acceptable, which calls for attention to the preparation of specialized cadres in the field of vocational education and the provision of professional concerns to suit the nature of the subject.